IMPLEMENTASI KONSEP TRIPLE BOTTOM LINE DALAM PROGRAM CORPORATE SOCIAL RESPONSIBILITY DI HOTEL ALILA SEMINYAK - Ni Nengah Ariastini; I Made Trisna Semara (Institut Pariwisata dan Bisnis Internasional, 2019)
The concept of the Triple Bottom Line (TBL) confirms that in running a business, companies do not only pay attention to profits, but also contribute to society (people), and play an active role in protecting the environment (planet). One implementation of the TBL concept is the Corporate Social Responsibility (CSR). Alila Seminyak is one of the hotels that have been implemented CSR. However, the community stated that there were deficiencies in the program. Even though the company stated there were no obstacles during the program implementation. The purpose of this study is to find out how was the implementation of TBL concept in the CSR program at Alila Seminyak and how the evaluation of the program. The data collection techniques used are documentation study, in-depth interviews, and observations. The data analysis technique used is qualitative descriptive analysis technique. The results of the study are Alila Seminyak has implemented the TBL concept in CSR programs but it has not been maximized in the concept of people. The people are not involved in the planning and evaluation of the program, and evaluation of the program has not been carried out optimally, because it does not involve the recipient community and there is no evaluation of the achievement of program objectives.